Severity and Association of Hypertensive Retinopathy in Patients with Chronic Kidney Disease Stages 3–5 (IAHS Medical Journal, 2026)
Background: Chronic Kidney Disease (CKD) is strongly associated with microvascular complications and Hypertensive Retinopathy (HR) is one of the key ocular manifestations. Since both the renal and retinal vasculatures are highly susceptible to long-standing hypertension, the severity of HR may reflect the progression of CKD. However, data are limited regarding the association between CKD stages and HR severity in our setting. To evaluate the severity and association of hypertensive retinopathy among patients with CKD stages 3–5 this study was done.Materials and methods: This cross-sectional study was conducted among 200 patients with CKD stages 3–5.Baseline demographic and clinical data, including age, gender, BMI, duration of hypertension and diabetes, and blood pressure measurements, were recorded using convenient sampling. Ocular examination included assessment of Best Corrected Visual Acuity (BCVA) using the LogMAR scale and grading of HR based on standard classification.Results: In this study of 200 CKD patients, the majority were over 50 years of age, male and overweight with a longstanding history of hypertension and diabetes. Distribution across CKD stages showed nearly equal proportions in stages 3, 4 and 5. Visual assessment revealed a significant decline in best corrected visual acuity with CKD progression, as poorer vision was more frequent in stages 4 and 5 compared to stage 3. Retinopathy assessment showed hypertensive retinopathy in more than half of the patients. Importantly, the severity of hypertensive retinopathy showed a significant association with CKD stage with advanced stages predominantly exhibiting higher grades (Grade 3–4) compared to earlier stages. These findings confirm that progressive CKD is strongly linked with worsening visual outcomes and more severe hypertensive retinopathy.Conclusion: The study demonstrated a significant association between advancing CKD stage and worsening severity of hypertensive retinopathy. Patients in CKD stages 4 and 5 exhibited higher grades of HR and poorer visual outcomes compared to those in stage 3. These findings suggest that retinal examination may serve as a simple, noninvasive marker of systemic vascular damage and should be integrated into routine monitoring of patients with CKD.IAHS Medical Journal Vol 8(2), December 2025; 55-59